True Womanhood in Hollywood: Gendered Business Strategies and the Rise and Fall of the Woman Filmmaker, 1896–1928 - Mahar, Karen Ward (Enterprise & Society, 2001)
Women flourished as producers, directors, screenwriters, and editors in the first quarter-century of the film industry. But by 1925 their presence in all but screenwriting was severely diminished. The argument of this essay is that the process of gendering the industry ultimately closed studio doors to female filmmakers. As studios moved from the artistic and entrepreneurial stage, conducive to the perceived qualities of women, to the corporate stage, the needs of the industry became masculinized and women were excluded. This process is explored by examining the assumptions regarding gender inherited by the early movie industry and the context in which gender was discussed within the industry, and by asking whether explicit assumptions about the fitness of women and men were ever factors in determining what and who a filmmaker should be.
Keywords: Business History and gender